Analisis Pengaruh Daya Tarik Iklan dan Celebrity Endorser terhadap Minat Beli Konsumen dimoderasi oleh Store Atmosphere (Studi pada Konsumen KFC Gajah Mada Medan) - delvi syahfitri (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2019)
The purpose of this research was to analyze the influenced of advertisement and celebrity endorser toward consumer buying interest moderated by store atmosphere (KFC Gajah Mada Medan consumer study). The type of research using associative with quantitative approach, the population of consumers who came to KFC Gajah Mada Medan as many as 15,281 consumers. Sampling using random samples with Slovin formula so that the number of samples as many as 100 respondents. Sources of research data using primary data and data collection techniques using surveys. Data analysis techniques used multiple linear regression, classical assumption test and hypothesis test. Based on the results of research indicated that the attractiveness of advertisement and celebrity endorser partially and simultant have an effected signifikan toward consumer buying interest in KFC branch of Gajah Madah Medan. Store atmosphere has aignificant effected toward consumer buying interest. Store atmosphere did not modify the influenced of advertising attraction and celebrity endorser toward consumer buying interest in KFC Gajah Mada Medan.